Lexical Density and Readability of the Facil’s ‘Advanced Learning Textbook’ for Indonesian High School Students - Dita Rizkiani; Sutiono Mahdi; Eva Tuckyta Sari Sujatna (AL-ISHLAH: Jurnal Pendidikan, 2022)
This article discusses the lexical density and readability levels in Facil's 'Advanced Learning English textbook for high school students in grade XI. The documents of this study were 11 reading texts selected from each chapter in the 'Advanced Learning English 2' textbook. This study's objectives are to (1) determine the average lexical density of selected reading passages from English textbooks and (2) determine the next level of this book and whether it is appropriate for high school students class XI. Grounded on Ure’s (1971) text analysis, the researchers analyzed the lexical density of the reading text. Meanwhile, to determine readability level, Flesch’s (1994) reading ease scale formula was utilized. After carefully analyzing the data, it was discovered that almost all texts had a high lexical density. The average reading text in this book has a higher lexical density level than 40%. Additionally, eleven reading texts are classified into five levels based on the Flesch reading ease formula's results: easy for one text, fairly easy for three texts, and difficult for four texts. For two texts, the difficulty level is standard; for three texts, the difficulty level is fairly difficult; and for two, the difficulty level is difficult. Therefore, reading texts in this book is considered appropriate for high school students’ learning process because each text has a different and gradual difficulty level.